Likely malarial etiology of hyperostosis espongio (symmetrical osteoporosis Hrdlicka) found in the skulls of the ancient Peruvians - Weiss, Pedro (1956)
I'll comment from the point of view of their possible patoqenia and prehistoric epidemiology, a curious process of bone, often in cemeteries gentilicios the Peruvian coast and elsewhere in America, from what I know, in tropical and subtropical. This known by a name that is not his illness, because it is Osteoporosis in pathologic sense, not necessarily symmetric, has been studied before by doctors, anthropologists and archaeologists, which explains the ambiguity in their names and in some interpretations of it have been made.